2011
DOI: 10.1016/j.ejcts.2011.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis on the use of the Heartstring anastomotic device to prevent stroke in patients undergoing off-pump coronary artery bypass grafting

Abstract: The results of this meta-analysis suggest that the risk of stroke after OPCAB may not be markedly reduced by the use of Heartstring device. On the other hand, a rather low rate of stroke was observed among patients with diseased ascending aorta indicating its potential value in these patients. Most of studies included in this meta-analysis were of poor methodological quality, and properly conducted prospective studies are needed to get more conclusive results on the safety and efficacy of Heartstring anastomos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In addition, we used proximal anastomotic device in patients with calcified ascending aorta, as Gold, et al 26) and Biancari, et al reported before. 27) Taken together, these precautions might contribute to the similar peri-procedural stroke rate in our CABG patients comparing with PCI. However, larger study is needed before any conclusions can be made.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, we used proximal anastomotic device in patients with calcified ascending aorta, as Gold, et al 26) and Biancari, et al reported before. 27) Taken together, these precautions might contribute to the similar peri-procedural stroke rate in our CABG patients comparing with PCI. However, larger study is needed before any conclusions can be made.…”
Section: Discussionmentioning
confidence: 82%
“…Similar results have been reported by other investigators. 2,8,36) To the best of our knowledge, cerebral microembolization of atheromatous material during manipulation of the aorta is the main cause of postoperative stroke. 23,24) Neurologic derangement after CABG has been attributed to hypoxia, embolism, hemorrhage, and metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Use of off-pump surgery and a no-touch aorta technique in the case of diseased ascending aorta, 28,29 improving CPB techniques and materials, 30 reducing CPB and aorta clamping times, 31 and avoidance of intraoperative hypoperfusion, 32 are measures which may significantly reduce the risk of postoperative CVA.…”
Section: Discussionmentioning
confidence: 99%